A dual-site based mixed matrix carbon molecular sieve membrane and a method of making the same
Patent Information
- Application Number
- CN202611444179.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-17
- Publication Date
- 2026-10-27
AI Technical Summary
但在现有的碳纳米球混合基质炭分子筛膜的主要制备流程为制备树脂纳米球、碳化为成品碳纳米球、活化、洗涤干燥、混入铸膜液、再整体碳化,该传统路线工序多,包含多次高温热处理、洗涤干燥以及粉体的后处理,操作繁琐,耗时久
[0022]1.简化工艺流程
Smart Images

Figure CN122974159A_ABST
Abstract
Description
[0001] This invention relates to the field of gas separation materials technology, and in particular to a dual in-situ mixed matrix carbon molecular sieve membrane and its preparation method. Background Technology
[0002] CO2 emissions from industrial and energy-related operations have been gradually increasing in recent years, leading to a year-on-year rise in atmospheric CO2 concentration. In the power generation sector, fossil fuels remain the primary energy source. CO2 is also a greenhouse gas, and increased emissions may lead to a series of environmental problems, including global warming, rising sea levels, and an increased probability of extreme weather events worldwide.
[0003] Currently, hydrogen is mainly produced through steam reforming (SMR) technology, which converts hydrocarbon fuels such as CH4 into H2, CO, and CO2. This technology is mature and has low cost, but it has high carbon emissions. Producing 1 kg of hydrogen will emit approximately 9-12 kg of CO2. Therefore, hydrogen production is also a significant source of carbon emissions. Different emission sources contain mixtures of CO2 and other gases, with wide variations in temperature, pressure, and composition. As a result, different types of CO2 separation technologies have been developed and utilized.
[0004] Hybrid matrix carbon molecular sieve membranes can be understood as a combination of hybrid matrix membranes and carbon molecular sieve membranes, inheriting the advantages of both while synergistically enhancing membrane performance. To overcome the bottleneck of the "trade-off" effect (permeability versus selectivity) in gas separation of traditional polymer membranes, inorganic porous fillers are incorporated into the polymer matrix, forming hybrid matrix membranes. Carbon molecular sieve membranes are produced by pyrolyzing polymer precursors (such as polyimide) at high temperatures and in an inert atmosphere, forming an internal structure similar to a molecular sieve. Compared to traditional polymer membranes, hybrid matrix carbon molecular sieve membranes exhibit superior resistance to high temperatures and pressures. Traditional polymer membranes are prone to plasticization under high pressure, leading to pore expansion and consequently a decrease in gas selectivity. In terms of corrosion resistance, hybrid matrix carbon molecular sieve membranes are more resistant to corrosive gases. Regarding separation performance, hybrid matrix carbon molecular sieve membranes offer advantages in both high selectivity and high permeability. In terms of stability, they can operate for a longer period without performance degradation compared to polymer membranes. However, the main preparation process of existing carbon nanosphere mixed matrix carbon molecular sieve membranes involves preparing resin nanospheres, carbonizing them into finished carbon nanospheres, activation, washing and drying, mixing them into casting solution, and then carbonizing them again. This traditional route has many steps, including multiple high-temperature heat treatments, washing and drying, and post-processing of the powder, making it cumbersome and time-consuming. Therefore, improving the process flow and simplifying the preparation process is an important direction for future development in the field of gas separation. Summary of the Invention
[0005] In view of the shortcomings of the aforementioned background technology, this invention proposes a dual in-situ mixed matrix carbon molecular sieve membrane and its preparation method. The specific technical solution is as follows: Resin nanospheres are prepared by solution blending of resin nanospheres, polyimide (PI), and anhydrous potassium carbonate to prepare a mixed matrix membrane, which is then carbonized at high temperature to form the mixed matrix carbon molecular sieve membrane. This invention employs a dual in-situ + one-step carbonization method, simultaneously mixing resin nanospheres (carbon nanosphere precursors) and anhydrous potassium carbonate activator into the PI casting solution. A single carbonization step simultaneously achieves in-situ generation of carbon nanospheres and dual in-situ activation of the membrane matrix and filler. Since the cross-linked resin nanospheres are insoluble in DMF, and anhydrous potassium carbonate is essentially insoluble in DMF, there is no need to consider the dissolution and loss of fillers and activators in the casting solution. The resin nanospheres can still be carbonized normally into carbon nanospheres at high temperatures. This invention requires only one blending and one carbonization step, significantly simplifying the process.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] A method for preparing a carbon molecular sieve membrane based on a dual in-situ mixed matrix, characterized by comprising the following steps:
[0008] Step 1: Disperse resorcinol in deionized water at 25℃, then add formaldehyde solution and stir until completely dissolved. Add n-propylamine to the system and stir for 0.5-3 h to obtain a homogeneous white solution. Then add 1.5-3 mol / L ammonia solution and stir the reaction at 60-90℃ for 4-8 h. After cooling to room temperature, centrifuge the reaction solution and wash it repeatedly with deionized water until neutral. The precipitate is freeze-dried for 24-48 h and then dried under vacuum at 80-120℃ for 12-24 h to obtain resin nanospheres. The ratio of resorcinol, deionized water, formaldehyde solution, n-propylamine, and ammonia solution is 1 g: 1500-3000 mL: 1-5 mL: 0.1-0.5 g: 2-10 mL.
[0009] Step 2: Place polyimide (PI) powder in a container and add ultra-dry N,N-dimethylformamide (DMF). Stir at 50~80℃ for 2~4 h until PI is completely dissolved to form a homogeneous solution. Filter to remove trace impurities from the system to obtain a PI matrix solution; wherein the mass ratio of PI to ultra-dry DMF is 1:4~20.
[0010] Step 3: Add the resin nanospheres obtained in Step 1 to ultra-dry DMF solvent, sonicate for 0.5-1 h, and stir for 1-5 h to obtain a resin nanosphere filler solution;
[0011] Step 4: Add the ground anhydrous potassium carbonate to ultra-dry DMF solvent, sonicate for 0.5-1 h, and then stir for 1-5 h to obtain a uniformly mixed activated solution; wherein the mass ratio of anhydrous potassium carbonate to DMF is 1:25~100.
[0012] Step 5: Take the PI matrix solution obtained in Step 2 into a container, add the filler solution obtained in Step 3, and then add the activation solution obtained in Step 4. Stir at room temperature for 0.5~2 h to mix the system evenly, then degas for 10-60 min. Coat the degassed casting solution evenly onto a flat substrate, dry at 60~80℃ for 10~15 h for preliminary solvent removal, and transfer to a vacuum condition at 100~120℃ for 12~24 h to deeply remove residual solvent, and obtain a resin nanosphere / PI mixed matrix film loaded with activator.
[0013] Step 6: Cut the mixed matrix membrane obtained in Step 5 into square pieces with a side length of 0.5-1.5 cm and place them between two layers of graphite plates. Carbonize them at 500-1000℃ under a nitrogen atmosphere to obtain a mixed matrix carbon molecular sieve membrane.
[0014] Step 7: Place the mixed matrix carbon molecular sieve membrane obtained in Step 6 in an ice-water bath and soak it in ice water for 10-30 min, then replace the ice water and repeat 1-5 times; then soak it in anhydrous ethanol for 5-20 min, then replace the anhydrous ethanol and repeat 1-3 times. After taking it out, air dry it at room temperature to obtain the mixed matrix carbon molecular sieve membrane.
[0015] Furthermore, the centrifugation conditions described in step 1 are 7000~12000 rpm and the time is 5~15 min.
[0016] Furthermore, the mass ratio of resin nanospheres to DMF in step 3 is 1:25~100;
[0017] Furthermore, in step 5, the mass ratio of the PI matrix solution obtained in step 2, the filler solution obtained in step 3, and the activation solution obtained in step 4 is 1:0.1~0.5:0.1~0.5.
[0018] Furthermore, the heating rate for carbonization in step 6 is 1~10℃ / min, and the holding time is 1~3 h.
[0019] Furthermore, a method for preparing a carbon molecular sieve membrane based on a dual in-situ mixed matrix is provided.
[0020] Furthermore, the mixed matrix carbon molecular sieve membrane prepared by this invention is used for CO2 / CH4 gas separation.
[0021] Compared with the prior art, the present invention has the following significant advantages:
[0022] 1. Simplify the process flow
[0023] This patent employs a "dual in-situ" preparation method, in which resin nanospheres are mixed with a uniformly dispersed activation solution into a polymer matrix to prepare a mixed matrix membrane. After a one-step solution blending to form a membrane, direct high-temperature carbonization yields a mixed matrix carbon molecular sieve membrane. Compared to existing technologies, which involve the cumbersome process of first preparing carbon nanospheres or pre-activating carbon materials followed by multiple composite and post-treatment steps to form a membrane, this invention achieves the in-situ conversion and activation of resin nanospheres to carbon nanospheres in a single high-temperature carbonization step. This significantly shortens the process flow, reduces operational complexity and energy consumption, and is beneficial for industrial-scale production.
[0024] 2. Synergistic effect of dual in-situ
[0025] In this invention, the volume shrinkage of the resin nanospheres during carbonization and the activation and pore-forming effect of anhydrous potassium carbonate occur simultaneously, synergistically creating a through-pore structure that is difficult to achieve using traditional stepwise methods. During activation, potassium carbonate reacts with elemental carbon at high temperature to generate potassium oxide and carbon monoxide. The etching effect of potassium carbonate consumes the elemental carbon in the membrane and the carbon nanospheres generated at high temperature, forming micropores on the membrane surface. The escape of the generated carbon monoxide also contributes to further pore formation. Compared with other pore-forming agents, the activation effect of anhydrous potassium carbonate is relatively mild and easy to control, enabling uniform pore formation on the carbon matrix and internal fillers, avoiding damage to the membrane structure from excessive etching. This results in a carbon molecular sieve membrane with both high specific surface area and suitable pore size distribution, providing favorable channels for preferential transport of gas molecules.
[0026] K₂CO₃ + C → K₂O + 2CO↑
[0027] 3. This invention uses DMF as the dispersion solvent to co-disperse resin nanospheres and anhydrous sodium carbonate in the casting solution. Since the resin nanospheres are already cross-linked and insoluble in DMF, this ensures their normal conversion into carbon nanospheres during subsequent carbonization, avoiding filler loss or agglomeration. Simultaneously, anhydrous potassium carbonate is also essentially insoluble in DMF, allowing for uniform dispersion and ensuring a consistent distribution of the activator during the carbonization stage. This method not only preserves the additional gas transport channels and molecular sieving effect provided by the pores of the carbon nanospheres themselves, effectively improving permeation flux and selectivity, but also achieves simultaneous activation of the in-situ generated carbon nanospheres, further enhancing their gas separation performance.
[0028] 4. This invention uses polyimide (PI) as the matrix material, whose excellent thermal stability and mechanical strength ensure the structural integrity of the membrane during high-temperature carbonization and practical applications. Simultaneously, the uniform dispersion of the filler in the polymer matrix and the good interfacial bonding between the filler and the matrix effectively suppress the plasticization of polymer segments under high pressure or long-term operation conditions and the resulting performance degradation, significantly enhancing the long-term operational stability of the membrane. Attached Figure Description
[0029] Figure 1 The X-ray diffraction patterns are those of Examples 1-2 and Comparative Examples 1-3.
[0030] Figure 2 The infrared spectra of Examples 1-2 and Comparative Examples 1-3 are shown. Detailed Implementation
[0031] The following examples illustrate the technical solutions of the present invention, but the scope of protection of the present invention is not limited to the examples listed:
[0032] All materials used in the following examples were commercially available. Resorcinol (99.0%) was purchased from SigmaLife Science, Germany; anhydrous potassium carbonate and formaldehyde solution (37 wt.%) were purchased from Sinopharm Chemical Reagent Co., Ltd.; n-propylamine (analytical grade) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; ammonia (25%) was purchased from Tianjin Damao Chemical Reagent Co., Ltd.; and DMF was purchased from Anhui Zesheng Technology Co., Ltd.
[0033] Example 1:
[0034] Step 1: Disperse 0.5 g of resorcinol in 800 mL of deionized water at 25 °C, then add 0.5 mL of formaldehyde solution and stir until completely dissolved. Add 0.07 g of n-propylamine to the system and stir for 1 h to obtain a homogeneous white solution. Then add 2 mL of 1.5 mol / L ammonia solution and stir the reaction at 85 °C for 5 h. After cooling to room temperature, repeatedly centrifuge and wash the reaction solution with deionized water at 10,000 rpm until neutral. The resulting precipitate is freeze-dried for 24 h and then vacuum-dried at 100 °C for 12 h to obtain resin nanospheres.
[0035] Step 2: Weigh 0.5 g of PI and place it in a container. Add 4.5 g of DMF and stir at 80°C for 3 h until completely dissolved to form a homogeneous solution. Then filter to remove trace impurities from the system to obtain the PI matrix solution.
[0036] Step 3: Add 0.1 g of the resin nanospheres prepared in Step 1 to 4.9 g of DMF, sonicate for 1 h and stir for 5 h to obtain the resin nanosphere filler solution.
[0037] Step 4: Add 0.1 g of ground anhydrous potassium carbonate to 4.9 g of DMF, sonicate for 1 h and stir for 5 h to obtain a uniformly mixed activated solution.
[0038] Step 5: Take 5 g of the PI solution prepared in Step 2 into a container, add 1.32 g of the filler solution obtained in Step 3, and then add 0.77 g of the activation solution obtained in Step 4. Stir at room temperature for 1.5 h to mix the system evenly, and then degas for 30 min. Coat the degassed casting solution evenly onto a flat substrate, and first dry at 60 °C for 15 h for preliminary solvent removal; then transfer to vacuum treatment at 120 °C for 24 h to deeply remove residual solvent, and obtain a resin nanosphere / PI hybrid matrix film loaded with activator.
[0039] Step 6: Cut the mixed matrix membrane obtained in Step 5 into 1 cm square pieces and place them between two graphite plates. In a nitrogen atmosphere, heat the membrane from room temperature to 700°C at a rate of 3°C / min and maintain the temperature for 2 hours to obtain a mixed matrix carbon molecular sieve membrane.
[0040] Step 7: Place the mixed matrix carbon molecular sieve membrane obtained in step 6 in an ice-water bath, soak it in ice water for 20 min, replace the ice water, repeat 3 times, then soak it in anhydrous ethanol for 10 min, replace the anhydrous ethanol, repeat 3 times, take it out and air dry at room temperature to obtain the mixed matrix carbon molecular sieve membrane.
[0041] exist Figure 1 In the XRD pattern, the prepared mixed matrix carbon molecular sieve membrane has a very obvious broad peak near 2θ=20°, which represents the carbon (002) plane diffraction peak, indicating that the membrane exhibits an amorphous amorphous morphology after high-temperature pyrolysis.
[0042] The separation performance of the prepared mixed matrix carbon molecular sieve membrane was tested and found to be P. CO2 =2498Barrer, CO2 / CH4=36.65.
[0043] Example 2:
[0044] Step 1: Disperse 0.5 g of resorcinol in 800 mL of deionized water at 25 °C, then add 0.5 mL of formaldehyde solution and stir until completely dissolved. Add 0.07 g of n-propylamine to the system and stir for 1 h to obtain a homogeneous white solution. Then add 2 mL of 1.5 mol / L ammonia solution and stir the reaction at 85 °C for 5 h. After cooling to room temperature, repeatedly centrifuge and wash the reaction solution with deionized water at 10,000 rpm until neutral. The resulting precipitate is freeze-dried for 24 h and then vacuum-dried at 100 °C for 12 h to obtain resin nanospheres.
[0045] Step 2: Weigh 0.5 g of PI and place it in a container. Add 4.5 g of DMF and stir at 80°C for 3 h until completely dissolved to form a homogeneous solution. Then filter to remove trace impurities from the system to obtain the PI matrix solution.
[0046] Step 3: Add 0.1 g of the resin nanospheres prepared in Step 1 to 4.9 g of DMF, sonicate for 1 h and stir for 5 h to obtain the resin nanosphere filler solution.
[0047] Step 4: Add 0.1 g of ground anhydrous potassium carbonate to 4.9 g of DMF, sonicate for 1 h and stir for 5 h to obtain a uniformly mixed activated solution.
[0048] Step 5: Take 5 g of the PI solution prepared in Step 2 into a container, add 1.32 g of the filler solution obtained in Step 3, and then add 1.59 g of the activation solution obtained in Step 4. Stir at room temperature for 1.5 h to mix the system evenly, then degas for 30 min. Coat the degassed casting solution evenly onto a flat substrate, and first dry at 60 °C for 15 h for preliminary solvent removal. Then transfer to vacuum treatment at 120 °C for 24 h to deeply remove residual solvent, and obtain a resin nanosphere / PI mixed matrix film loaded with activator.
[0049] Step 6: Cut the mixed matrix membrane obtained in Step 5 into 1 cm square pieces and place them between two graphite plates. In a nitrogen atmosphere, heat the membrane from room temperature to 700°C at a rate of 3°C / min and maintain the temperature for 2 hours to obtain a mixed matrix carbon molecular sieve membrane.
[0050] Step 7: Place the mixed matrix carbon molecular sieve membrane obtained in step 6 in an ice-water bath, soak it in ice water for 20 min, replace the ice water, repeat 3 times, then soak it in anhydrous ethanol for 10 min, replace the anhydrous ethanol, repeat 3 times, take it out and air dry at room temperature to obtain the mixed matrix carbon molecular sieve membrane.
[0051] exist Figure 1 In the XRD pattern, the prepared mixed matrix carbon molecular sieve membrane has a very obvious broad peak near 2θ=20°, which represents the carbon (002) plane diffraction peak, indicating that the membrane exhibits an amorphous amorphous morphology after high-temperature pyrolysis.
[0052] The separation performance of the prepared mixed matrix carbon molecular sieve membrane was tested and found to be P. CO2 =2611Barrer, CO2 / CH4=33.67.
[0053] Comparative Example 1:
[0054] Step 1: Weigh 0.5 g of PI and place it in a container. Add 4.5 g of DMF and stir at 80°C for 3 h until completely dissolved to form a homogeneous solution. Then filter to remove trace impurities from the system to obtain the PI matrix solution.
[0055] Step 2: Weigh 5 g of the PI solution prepared in Step 1 into a container and stir at room temperature for 1.5 h to mix the system evenly; then degas for 30 min, and uniformly coat the degassed casting solution onto a flat substrate. First, dry at 60℃ for 15 h to perform preliminary solvent removal; then transfer to vacuum treatment at 120℃ for 24 h to deeply remove residual solvent, and obtain a 10 wt.% PI polymer film.
[0056] Step 3: Cut the polymer membrane prepared in step 2 into 1 cm square pieces and place them between two graphite plates. In a nitrogen atmosphere, heat the membrane from room temperature to 700°C at a rate of 3°C / min and maintain the temperature for 2 h to obtain a carbon molecular sieve membrane.
[0057] exist Figure 1 The carbon molecular sieve membrane prepared in the XRD pattern has a very obvious broad peak near 2θ=20°, which represents the carbon (002) plane diffraction peak, indicating that the membrane exhibits an amorphous amorphous morphology after high-temperature pyrolysis.
[0058] The separation performance of the prepared mixed matrix carbon molecular sieve membrane was tested and found to be P. CO2 =2047Barrer, CO2 / CH4=32.24.
[0059] Comparative Example 2:
[0060] Step 1: Weigh 0.5 g of PI and place it in a container. Add 4.5 g of DMF and stir at 80°C for 3 h until completely dissolved to form a homogeneous solution. Then filter to remove trace impurities from the system to obtain the PI matrix solution.
[0061] Step 2: Add 0.1 g of ground anhydrous potassium carbonate to 4.9 g of DMF, sonicate for 1 h and stir for 5 h to obtain a uniformly mixed activated solution.
[0062] Step 3: Weigh 5 g of the PI solution prepared in Step 1 into a container, and add 0.77 g of the activation solution prepared in Step 2. Stir at room temperature for 1.5 h to ensure uniform mixing; then degas for 30 min. Coat the degassed casting solution evenly onto a flat substrate, and first dry at 60℃ for 15 h for preliminary solvent removal; then transfer to a vacuum treatment at 120℃ for 24 h to deeply remove residual solvent, obtaining a PI polymer film loaded with activator.
[0063] Step 4: Cut the polymer membrane prepared in step 3 into 1 cm square pieces and place them between two graphite plates. In a nitrogen atmosphere, heat the membrane from room temperature to 700°C at a rate of 3°C / min and maintain the temperature for 2 h to obtain a carbon molecular sieve membrane.
[0064] Step 5: Place the carbon molecular sieve membrane obtained in step 4 in an ice-water bath and soak it in ice water for 20 min. Replace the ice water and repeat 3 times. Then soak it in anhydrous ethanol for 10 min and replace it with anhydrous ethanol. Repeat 3 times. After taking it out, air dry it at room temperature to obtain a mixed matrix carbon molecular sieve membrane.
[0065] exist Figure 1 The carbon molecular sieve membrane prepared in the XRD pattern has a very obvious broad peak near 2θ=20°, which represents the carbon (002) plane diffraction peak, indicating that the membrane exhibits an amorphous amorphous morphology after high-temperature pyrolysis.
[0066] The separation performance of the prepared mixed matrix carbon molecular sieve membrane was tested and found to be P. CO2 =2186Barrer, CO2 / CH4=33.89.
[0067] Comparative Example 3:
[0068] Step 1: Disperse 0.5 g of resorcinol in 800 mL of deionized water at 25 °C, then add 0.5 mL of formaldehyde solution and stir until completely dissolved. Add 0.07 g of n-propylamine to the system and stir for 1 h to obtain a homogeneous white solution. Then add 2 mL of 1.5 mol / L ammonia solution and stir the reaction at 85 °C for 5 h. After cooling to room temperature, repeatedly centrifuge and wash the reaction solution with deionized water at 10,000 rpm until neutral. The resulting precipitate is freeze-dried for 24 h and then vacuum-dried at 100 °C for 12 h to obtain resin nanospheres.
[0069] Step 2: Weigh 0.5 g of PI and place it in a container. Add 4.5 g of DMF and stir at 80°C for 3 h until completely dissolved to form a homogeneous solution. Then filter to remove trace impurities from the system to obtain the PI matrix solution.
[0070] Step 3: Add 0.1 g of the resin nanospheres prepared in Step 1 to 4.9 g of DMF, sonicate for 1 h and stir for 5 h to obtain the resin nanosphere filler solution.
[0071] Step 4: Take 5 g of the PI solution prepared in Step 2 into a container, add 1.32 g of the filler solution obtained in Step 3, stir at room temperature for 1.5 h to mix the system evenly, then degas for 30 min, and uniformly coat the degassed casting solution onto a flat substrate. First, dry at 60℃ for 15 h to perform preliminary solvent removal; then transfer to 120℃ for vacuum treatment for 24 h to deeply remove residual solvent, and obtain a resin nanosphere / PI mixed matrix film.
[0072] Step 5: Cut the mixed matrix membrane prepared in step 4 into 1 cm square pieces and place them between two graphite plates. In a nitrogen atmosphere, heat the membrane from room temperature to 700°C at a rate of 3°C / min and hold for 2 h. After cooling, remove the membrane to obtain the mixed matrix carbon molecular sieve membrane.
[0073] exist Figure 1 The carbon molecular sieve membrane prepared in the XRD pattern has a very obvious broad peak near 2θ=20°, which represents the carbon (002) plane diffraction peak, indicating that the membrane exhibits an amorphous amorphous morphology after high-temperature pyrolysis.
[0074] The separation performance of the prepared mixed matrix carbon molecular sieve membrane was tested and found to be P. CO2 =2294Barrer, CO2 / CH4=34.81.
[0075] The filler content, activator content, CO2 permeability coefficient, and CO2 / CH4 selectivity of Comparative Examples 1-3 and Examples 1-3 are shown in Table 1.
[0076] Table 1. Preparation parameters and gas separation performance of the examples and comparative examples
[0077] Comparative Example 1 0 0 2047 32.24 Comparative Example 2 0 3 2186 33.89 Comparative Example 3 5 0 2294 34.81 Example 1 5 3 2498 36.65 Example 2 5 6 2611 33.67
[0078] like Figure 2As shown, comparing the infrared spectra of each embodiment with the comparative example, although the intensity of the absorption peaks varies to some extent, the overall spectral characteristics conform to the structural characteristics of PI-based carbon molecular sieve membranes, and no new characteristic absorption peaks appear, indicating that there is only a physical interaction between the filler and the functional groups of the PI polymer matrix, and no chemical reaction occurs. Combined with the broad-area diffraction peaks of amorphous carbon (002) observed in the X-ray diffraction pattern, this further confirms that the resin nanospheres were successfully transformed into carbon nanospheres after high-temperature carbonization. The test results in Table 1 show that the permeability coefficients of each embodiment are significantly better than those of the comparative example. In terms of selectivity, Example 1 exhibits better CO2 / CH4 selectivity, while the selectivity of Example 2 decreases slightly due to over-activation caused by the higher content of anhydrous potassium carbonate, but the permeability coefficient is further improved. Overall, the comprehensive performance of each embodiment is significantly better than that of the comparative example. In practical applications, if a balance of comprehensive performance is sought, Example 1 is a better choice; if permeation is the primary objective, Example 2 is more advantageous.
[0079] The above description is merely a specific embodiment of the present invention, enabling those skilled in the art to understand or implement the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention is not to be limited.
Claims
1. A method for preparing a carbon molecular sieve membrane based on a dual in-situ mixed matrix, characterized in that, Includes the following steps: Step 1: Disperse resorcinol in deionized water at 25℃, then add formaldehyde solution and stir until completely dissolved. Add n-propylamine to the system and stir for 0.5-3 h to obtain a homogeneous white solution. Then add 1.5-3 mol / L ammonia solution and stir the reaction at 60-90℃ for 4-8 h. After cooling to room temperature, centrifuge the reaction solution and wash it repeatedly with deionized water until neutral. The precipitate is freeze-dried for 24-48 h and then dried under vacuum at 80-120℃ for 12-24 h to obtain resin nanospheres. The ratio of resorcinol, deionized water, formaldehyde solution, n-propylamine, and ammonia solution is 1 g: 1500-3000 mL: 1-5 mL: 0.1-0.5 g: 2-10 mL. Step 2: Place polyimide (PI) powder in a container and add ultra-dry N,N-dimethylformamide (DMF). Stir at 50~80℃ for 2~4 h until the PI is completely dissolved to form a homogeneous solution. Filter to remove trace impurities from the system to obtain the PI matrix solution. The mass ratio of PI to ultra-dry DMF is 1:4~20; Step 3: Add the resin nanospheres obtained in Step 1 to ultra-dry DMF solvent, sonicate for 0.5-1 h, and stir for 1-5 h to obtain a resin nanosphere filler solution; Step 4: Add the ground anhydrous potassium carbonate to ultra-dry DMF solvent, sonicate for 0.5-1 h, and then stir for 1-5 h to obtain a uniformly mixed activated solution; wherein the mass ratio of anhydrous potassium carbonate to DMF is 1:25~100. Step 5: Take the PI matrix solution obtained in Step 2 into a container, add the filler solution obtained in Step 3, and then add the activation solution obtained in Step 4. Stir at room temperature for 0.5~2 h to mix the system evenly, then degas for 10-60 min. Coat the degassed casting solution evenly onto a flat substrate, dry at 60~80℃ for 10~15 h for preliminary solvent removal, and transfer to a vacuum condition at 100~120℃ for 12~24 h to deeply remove residual solvent, and obtain a resin nanosphere / PI mixed matrix film loaded with activator. Step 6: Cut the mixed matrix membrane obtained in Step 5 into square pieces with a side length of 0.5-1.5 cm and place them between two layers of graphite plates. Carbonize them at 500-1000℃ under a nitrogen atmosphere to obtain a mixed matrix carbon molecular sieve membrane.
2. Step 7: Place the mixed matrix carbon molecular sieve membrane obtained in step 6 in an ice-water bath, soak it in ice water for 10-30 min, replace the ice water, and repeat 1-5 times; then soak it in anhydrous ethanol for 5-20 min, replace the anhydrous ethanol, and repeat 1-3 times. After taking it out, air dry it at room temperature to obtain the mixed matrix carbon molecular sieve membrane.
3. The method for preparing a carbon molecular sieve membrane based on a dual in-situ mixed matrix according to claim 1, characterized in that, The centrifugation conditions described in step 1 are 7000~12000 rpm and the time is 5~15 min.
4. The method for preparing a carbon molecular sieve membrane based on a dual in-situ mixed matrix according to claim 1, characterized in that, The mass ratio of resin nanospheres to DMF in step 3 is 1:25~100.
5. The method for preparing a carbon molecular sieve membrane based on a dual in-situ mixed matrix according to claim 1, characterized in that, In step 5, the mass ratio of the PI matrix solution obtained in step 2, the filler solution obtained in step 3, and the activation solution obtained in step 4 is 1:0.1~0.5:0.1~0.
5.
6. The method for preparing a carbon molecular sieve membrane based on a dual in-situ mixed matrix according to claim 1, characterized in that, The carbonization heating rate in step 6 is 1~10℃ / min, and the holding time is 1~3 h.
7. The carbon molecular sieve membrane based on a dual in-situ mixed matrix prepared by the method for preparing a dual in-situ mixed matrix carbon molecular sieve membrane according to any one of claims 1 to 5.
8. The carbon molecular sieve membrane based on a dual in-situ mixed matrix according to claim 6, characterized in that, The mixed matrix carbon molecular sieve membrane prepared by this invention is used for CO2 / CH4 gas separation.